The Snow Dragon: China’s Strategies in the Arctic - Alexeeva, Olga V.; Lasserre, Frédéric (Centre d'études français sur la Chine contemporaine, 2016)
In recent years, several analyses and news media articles have predicted a resurgence of tensions in the Arctic over access to maritime space. Among the contenders involved in this potential struggle is China, whose ambitions in the region are suspected to hold a destabilising potential. Yet, as Beijing is developing its policy towards the region, it remains unclear whether it will contest the claims over maritime access of countries bordering the Arctic and forcibly take over parts of the region for resource extraction purposes.